Pathogenicity and Molecular Typing of Fowl Adenovirus-Associated With Hepatitis/Hydropericardium Syndrome in Central China (2015–2018) - Cui, Jin; Xu, Yingying; Zhou, Zutao; Xu, Qingrong; Wang, Jiaxiang; Xiao, Yuncai; Li, Zili; Bi, Dingren (Frontiers in Veterinary Science, 2020)
In central China, a large number of broiler and layer flocks have suffered from outbreaks of severe hepatitis/hydropericardium syndrome (HHS). This resulted in huge economic losses to the poultry industry, from 2015 to 2018. To identify the specific pathogen and study its pathogenicity, 195 samples from Hubei, Jiangxi, Anhui, Hunan and Henan provinces in central China were collected. The samples were screened for the adenovirus hexon gene and neighbor joining was used for the phylogenetic reconstruction of the sequences. Among the collected samples, 122 were found to be positive for fowl adenovirus (FAdV) by PCR and 73 isolates were obtained. The predominant viral serotype was serotype 4 (FAdV-4) which was found in 48 isolates, while 24 were serotype 10 (FAdV-10) and one was serotype 2 (FAdV-2). The CH/HBTF /1710 isolate was selected for further experiment and inoculated into 33-day-old specific pathogen-free chickens via intramuscular injection or oral administration to evaluate pathogenicity. It was found that the mortality for chickens infected by intramuscular injection or oral administration was 70% and 60%, respectively. Necropsy reveled mild to severe hepatitis and hydropericardium at five and seven days after infection. Ancestor analyses indicated that all of the FAdV-4 strains obtained in this study shared a common Indian precursor, and had a close genetic relationship with the JSJ13, SDSX, HN/151025 and SDDM-15 strains common in China.